Studi Komparatif Pemanfaatan Posyandu Lansia di Wilayah Pesisir dan Non Pesisir Kota Kendari - Mangalla, Feni Yasinta; Sety, La Ode Muhamad; n, Irma (Universitas Malahayati, 2024)
ABSTRACT Posyandu for the elderly is a community-based health service that focuses on promotive and preventive efforts for elderly health problems. The elderly population in the world has now entered the aging population era because it exceeds 7% of the total population. The number of elderly Posyandu targets in coastal areas is 1,029 people with a total visit of 895 people (87.0%) while the target number of elderly Posyandu in non-coastal areas is 1,271 people with a total visit of 743 elderly people (58.4%), this shows the utilization of Posyandu Elderly people in coastal areas, represented by the Abeli Community Health Center and non-coastal areas represented by the Mokau Community Health Center, have not yet reached the target. This research was conducted in October 2023. The aim of this research was to determine the differences in the utilization factors of Posyandu for the elderly in coastal areas and non-coastal areas. The type of research used is a quantitative research design with a cross sectional approach. The population in this study were all elderly people aged ≥ 60 years and registered as members of the elderly Posyandu in 2023. The total sample was 180 people, consisting of 88 respondents from the working area of the Abeli Health Center and 92 respondents from the working area of the Mokoau Community Health Center using sampling techniques. namely Simple Random Sampling. The instrument used was a structured questionnaire. Data were analyzed using the Mann Whitney test. The results of research in coastal and non-coastal areas show that there are statistical differences (ρ < 0.05) in the use of Posyandu (p = 0.582), perceptions of the elderly (ρ = 0.643), culture of seeking treatment (ρ = 0.002), family support (ρ = 0.001), and the role of cadres (ρ = 0.960). The conclusion from the results of this research is that there is a need for activities to increase understanding through counseling for the elderly and their families regarding health problems that exist in the elderly Posyandu. Keywords: Utilization, Perception, Culture of Seeking Treatment, Family Support, Role of Cadres ABSTRAK Posyandu lansia merupakan wadah pelayanan kesehatan berbasis masyarakat yang berfokus pada upaya promotif dan preventif masalah kesehatan lansia. Populasi lansia di dunia saat ini sudah memasuki era penduduk menua (ageing population) kaerena melebihi angka 7% dari jumlah populasi penduduk. Jumlah sasaran Posyandu lansia di wilayah pesisir sebesar 1.029 jiwa dengan total kunjungan 895 jiwa (87,0%) sedangkan sasaran Posyandu lansia di wilayah non pesisir sebesar 1.271 jiwa dengan total kunjungan lansia 743 jiwa (58,4%), hal ini menunjukkan pemanfaatan Posyandu lansia di wilayah pesisir yakni diwakilkan Puskesmas Abeli dan wilayah non pesisir diwakilkan Puskesmas Mokau belum mencapai target. Penelitian ini dilakukan pada bulan oktober tahun 2023. Tujuan penelitian ini untuk mengetahui perbedaan faktor pemanfaatan Posyandu lansia di wilayah pesisir dan wilayah non pesisir. Jenis penelitian yang digunakan adalah desain penelitian kuantitatif dengan pendekatan Cross Sectional. Populasi dalam penelitian ini merupakan seluruh lansia yang berumur ≥ 60 tahun dan terdaftar sebagai anggota Posyandu lansia pada tahun 2023. Total sampel berjumlah 180 jiwa, terdiri dari 88 responden dari wilayah kerja Puskesmas Abeli dan 92 responden dari wilayah kerja Puskesmas Mokoau dengan menggunkan teknik pengambilan sampel yakni Simple Random Sampling. Instrumen yang digunakan yakni kuesioner terstruktur. Data di analisis dengan menggunakan uji Mann Whitney. Hasil penelitian di wilayah pesisir dan non pesisir menunjukkan ada perbedaan secara statistik (ρ < 0,05) pemanfaatan Posyandu (p = 0,582), persepsi lansia (ρ = 0,643), budaya pencarian pengobatan (ρ = 0,002), dukungan keluarga (ρ = 0,001), dan peran kader (ρ = 0,960). Kesimpulan dari hasil penelitian ini adalah perlu adanya kegiatan peningkatan pemahaman melalui penyuluhan kepada lansia dan keluarga mengenai masalah kesehatan yang ada di Posyandu lansia. Kata Kunci: Pemanfaatan , Persepsi, Budaya Pencarian Pengobatan, Dukungan Keluarga, Peran Kader